Molecular interactions of Gas Chromatography – Mass Spectrometry (GC-MS) and HPLC Characterization of Alstonia Boonei and Ficus Exasperata Leaves Methanol Extracts - Aguebor-Ogie, Nogiomwan Bobby; Osagie, Augustine Ododo (International Journal of Scientific Research in Biological Sciences, 2025)
Alstonia boonei is a well-known plant whose components are high in bioactive chemicals such echitamidine, boonein, lupeol, ursolic acid, loganin, N- formylechitamidine and b-amyrin, with triterpenoids and alkaloids accounting for a large fraction of the total bioactive compound while Ficus exasperata Vahl. (F. exasperata) sometimes known as "Sandpaper Leaf Tree" because of the coarse surface of its leaves, is utilized for the management of various diseases, and as a result, research supporting traditional uses are expanding According to reports, F. exasperata leaves have anti-ulcer, oxytocin inhibiting, anticonvulsant, antinociceptive, antipyretic, anti-inflammatory, antimicrobial, anxiolytic, hypolipidemic, anti-candidal, insecticidal, hypoglycemic, and pesticidal propertie. The leave of Ficus exasperata' and Alstonia boonei were dried in a laboratory environment devoid of direct sunlight till completely dry, after which they were extratec using methanol and then rotaroy evaporated to collect the extracts. Both the GC-MS and HPLC analyses revealed the presence of some biochemically useful hydrocarbons while the molecular docking results revealed the potential usefulness of some of these compounds as medicinal compounds as a result of the binding energies.